The level of critical thinking skills of nursing students at International Islamic University Malaysia (IIUM), Kuantan, Pahang - Ruslan, Aisyah; Ruslan, Rusila (IIUM Press, 2024)
Background: Critical thinking is a vital competence in the nursing profession, essential for providing safer and higher-quality patient care. The rapid evolution and constant changes in the healthcare industry necessitate a teaching and learning environment that offers ample opportunities for students to engage in activities that enhance critical thinking, beyond traditional role-playing methods. This study aims to assess the level of critical thinking among undergraduate nursing students at International Islamic University Malaysia (IIUM) Kuantan Campus, Pahang, Malaysia. Methods: A quantitative cross-sectional study was conducted using an online survey. Participants were selected based on inclusion and exclusion criteria. The brief version of the Critical Thinking Disposition Inventory (CTDI-CV) questionnaire was utilized. All undergraduate students at the Kulliyyah of Nursing were invited to complete the survey online. The data were analysed using ChiSquare and descriptive statistics. Results: A total of 152 students participated in the online survey. Results showed that 54.6% of respondents demonstrated strong critical thinking ability, with a mean critical thinking score of 72.14. Analysis of the socio-demographic profiles showed a significant correlation between the level of critical thinking and gender and year of study with p-values of 0.018 and 0.038 respectively. Conclusion: The study highlights the need for more effective teaching strategies specifically designed to promote critical thinking skills in nursing students.